Water resources on outer-lying islands in Micronesia - Beikmann, Alise Marie, author; Bailey, Ryan, advisor; Ettema, Robert, committee member; Grigg, Neil, committee member; Ronayne, Michael, committee member (Colorado State University. Libraries, 2016)
To view the abstract, please see the full text of the document.
Keywords: drought; atoll; rainwater; groundwater; Micronesia